Viabilidade agroeconômica em associações de cenoura e caupi-hortaliça em ambiente semiárido - Silva, Josimar Nogueora da (Universidade Federal Rural do Semi-Árido, 2019)
The intercropping system is an alternative crop, which when combined with the choice of the appropriate amount of green manure and of the best spatial arrangement is an important option to promote a better ecosystem equilibrium. Thus, the objective of this study was to evaluate agroeconomic viability in carrot and vegetable cowpea associations in semi-arid environment, as a function of amounts of Merremia aegyptia biomass incorporated into the soil and of spatial arrangements in two growing seasons in semiarid environment. Two experiments were conducted under field conditions at the Rafael Fernandes Experimental Farm, Mossoró, RN, Brazil from July to October 2017 and 2018. The experimental design was a randomized block design with treatments arranged in a 4 x 3 factorial scheme, with four replications. The first factor was constituted by the quantities of M. aegyptia (20; 35, 50 and 65 t ha-1 in dry basis) and the second factor by the spatial arrangements (2: 2, 3: 3 and 4: 4), corresponding to the rows of carrot alternated with rows of vegetable cowpea. They were evaluated in the carrot: shoot and root dry mass, total and commercial productivity of roots and classified productivity of roots in long, medium, short and scrap. In the vegetable cowpea, it was evaluated: number of green grains per pod, weight of 100 green grains, yield and dry mass of green grains. The bio-agroeconomic indexes evaluated in the intercropping system were: land equivalent coefficient, monetary equivalent ratio, land equivalent ratio, area time equivalent ratio in time, score of the canonical variable, actual yield loss, intercropping advantage, gross income, net income, rate of return, and profit margin. The agronomic optimization of carrot and vegetable cowpea in intercropping was achieved with the amounts of 32.69 and 50.17 t ha-¹ of M. aegyptia biomass incorporated into the soil, respectively. The 2: 2 spatial arrangement provided greater agroeconomic efficiency in the intercropping and improved productive performance of cowpea. The greater bio-agroeconomic viability of the carrot and vegetable cowpea intercropping was obtained in the amounts of 47.82 and 36.60 t ha-1 of M. aegyptia incorporated to the soil, respectively. The second growing season provided greater agroeconomic viability of the association of carrot and vegetable cowpea
Keywords: Daucus carota; Vigna unguiculata; Merremia aegyptia; Associação de culturas; Eficiência agroeconômica; Daucus carota; Vigna unguiculata; Merremia aegyptia; Association of cultures; Agroeconomic efficiency; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA